Italian version of the Assessment of Interprofessional Team Collaboration Scale II (I-AITCS II): a multiphase study of validity and reliability amongst healthcare providers - Caruso, Rosario; Magon, Arianna; Dellafiore, Federica; Griffini, Sara; Milani, Laura; Stievano, Alessandro; Orchard, Carole A. (La Medicina del Lavoro, 2018)
Objective: To develop and validate an Italian version of the Assessment of Interprofessional Team Collaboration Scale II (I-AITCS II). Methods: A multiphase validation study was conducted. The first phase was the AITCS-II translation from English into Italian to develop the first version of I-AITCS II for practitioners. The second phase was the study of I-AITCS II face and content validity, and the third phase was a cross-sectional data collection to provide evidence of construct validity using the psychometrics testing and the reliability assessment through the internal consistency study. Results: The agreement for the forward-translation among researchers was high. The face and content validity were satisfactory. The underlying constructs of I-AITCS II were partnership, cooperation and coordination. Internal consistency was good for both scale and domains level. There were significant differences related to partnership in the comparison between settings. Conclusions: I-AITCS II showed evidence of validity and reliability. It will be useful to gather data to address programs aimed to enhance interprofessional team collaboration within the Italian healthcare contexts, and it could be used for cross-national researches.